Profiles of sleep status among older adults in New Zealand : the association between alcohol use and other health and lifestyle factors : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Bioscience at Massey University, Wellington, New Zealand - Jones, Courtney Jayde (Massey University, 2022)
Sleep is a crucial determinant and modifiable factor of health and well-being that changes continuously throughout life. Changes in sleep are partly owing to physiological ageing alongside individual-level, social-level and societal-level factors. By 2050, approximately one-quarter of people living in New Zealand will be 65 years or older. The ageing population structure of New Zealand is of interest given the numerous social, physiological and behavioural changes that occur with ageing, and impacts social, economic, and health landscapes in New Zealand. Older adults today drink more alcohol than previous generations have, and research shows that alcohol use is clearly associated with sleep disturbance in younger adults. Given the clear links between alcohol use, sleep and ageing, it is concerning that there is a paucity of research on older adults, despite older adults being at a significantly higher risk of alcohol-related harm and poor sleep. The following thesis, therefore, investigated the role of alcohol on the sleep of older adults by (1) distinguishing profiles of sleep, (2) determining the sociodemographic and health differences that underpin each profile in older adulthood, and (3) investigating how alcohol use was associated with profiles of sleep status in older adult drinkers. An analysis of 2013/2014 New Zealand Health Survey data was conducted. Information of 13,309 adults ≥ 15 years old was analysed, of whom 22% (2,932) were older adults (≥ 65 years; 56.51% female; 21.32% Māori). There were five sleep profiles established using available sleep items. These were established according to whether a respondent: (a) reported having a diagnosed sleep disorder; (b) experienced frequent daytime sleepiness; reported a usual sleep duration consistent with (c) short sleep; (d) long sleep, or (e) typical sleep as assessed against the National Sleep Foundation’s ‘Appropriate Sleep Duration’ guidelines. Demographic, health and alcohol use differences between older (65+ years) and younger (15–64 years) participants and sleep profiles were explored. Demographic and health differences between sleep profiles in the older sample were investigated. Multinomial models were performed to determine the key factors that underpinned each sleep profile in older adulthood, followed by an assessment of how alcohol use altered the membership of factors that underpinned sleep profiles for older adults. In this study, 21.21% of all respondents were categorised within the poor sleep profiles (i.e., presence of sleep disorder, frequent daytime sleepiness, short sleep or long sleep). The prevalence of poor sleep was significantly greater among older adults (27.76%) compared to younger adults (19.35%). Older adults were more likely to be associated with the ‘sleep disorder’, ‘excessive sleepiness’, or ‘long sleep’ profiles. By contrast, younger adults were more likely to be short or typical sleepers. Statistical models demonstrated multimorbidity and polypharmacy were significant predictors of the sleep disorder profile for older adults. Older adult long sleepers were more likely to be of later age, male and have poor nutrition intake. Typical sleep in older adulthood was significantly associated with better health and socioeconomic status. Older adults profiled as ‘excessively sleepy’ were more likely to be older, male, Māori or have a higher body mass index. Higher quantity consumption (three or more drinks) was a significant factor for membership of the excessive sleepiness profile among older adult drinkers. This research progresses the understanding of the relationship between sleep and alcohol use among older adults in New Zealand. This thesis contributes to the understanding of the key demographic and health factors that coincide with profiles of sleep in older adults.
Keywords: 420606 Social determinants of health